Modeling the Relationships between Differentiation and Cognitive Emotion Regulation in Mothers with Children's Anxiety: The Mediating Role of Maternal Mental Health - Farahbakht, Marzieh; Rezaei Dehnavi, Sedigheh (Shahroud Journal of Medical Sciences, 2024)
Background: Children, like adults, experience anxiety when faced with new experiences and different situations. The present study aimed to model the relationships between differentiation and cognitive emotion regulation in mothers with children's anxiety, with the mediating role of maternal mental health.Methods: The research belonged to the category of correlation designs. The target population of the study consisted of all mothers residing in Shiraz in 2019. The sample in the present study consisted of 200 mothers residing in Shiraz. The sample individuals were selected using the cluster sampling method for the research. The instruments used in the present study included the Differentiation of Self Inventory (DSI), the Beck Anxiety Inventory (BAI), Garnefski’s Cognitive Emotion Regulation Questionnaire, and the General Health Questionnaire. The obtained results were analyzed using the Amos test.Results: Findings indicated that the differentiation of mothers does not directly impact children's anxiety significantly (P-value=0.311, β=0.052). However, this factor does have a positive influence on mental health (P-value=0.000, β=0.411). Similarly, the cognitive regulation of mothers can be used to predict children's anxiety. The results from the table demonstrate that mental health has a direct negative effect on children's anxiety (β=-0.298, P-value<0.001). Negative strategies also contribute negatively to mental health (P-value=0.030, β=-0.169) and positively to child anxiety (P-value<0.001, β=0.847). On the other hand, positive strategies do not directly impact child anxiety significantly (P-value=0.916, β=0.01), but they do have a positive and significant effect on mental health (P-value<0.001, β=0.624).Conclusions: The results indicated that differentiation in mothers and positive cognitive emotion regulation strategies lead to improved maternal mental health and reduced anxiety in children. Additionally, differentiation and negative cognitive emotion regulation strategies result in increased anxiety in children and reduced maternal mental health.